Solve x2−xy+y2=7 for x. x=2y−228−3y2,x=2y+228−3y2Substitute 2y−228−3y2 for x in 2x−y=5 and simplify. 2x−y2(2y−228−3y2)−y28−3y2=5=5=−5Substitute 2y−228−3y2 for x in 2x−y=5 and simplify. 2x−y2(2y−228−3y2)−y28−3y2=5=5=−5Substitute 2y+228−3y2 for x in 2x−y=5 and simplify. 2x−y2(2y+228−3y2)−y28−3y2=5=5=5Substitute −1 into x2−xy+y2=7 to solve for x. x2−x(−1)+(−1)2x2+x+1x2+x−6(x−2)(x+3)x=−3=7=7=0=0,x=2This yields the following solution. x=2,y=−1Substitute 1 into x2−xy+y2=7 to solve for x. x2−x1+12x2−x+1x2−x−6(x−3)(x+2)x=−2=7=7=0=0,x=3This yields the following solution. x=3,y=1